Comparative Analysis on the Adoption and Use of BIM in Road Infrastructure Projects - Chong, Heap Yih; Lopez, Robert; Wang, Jun; Wang, Xiangyu; Zhao, Z. (ASCE, 2016)
© 2016 American Society of Civil Engineers.The uses of building information modeling (BIM) in building and infrastructure projects are numerous. Most previous BIM case examples focused on buildings, and limited studies have reported on the adoption and use of BIM in infrastructure projects. Therefore, this research aims to analyze and compare the adoption and use of BIM in infrastructure projects, particularly in constructing major road projects in Australia and the People's Republic of China. The related BIM uses and associated technologies of the projects were analyzed based on a case study approach. Subsequently, a number of comparative analyses were conducted on the cultural and managerial aspects between the projects, as well as different BIM uses between buildings and infrastructure projects. The results show both case studies had quite similar uses of BIM, yet the adopted managerial strategies and issues encountered were rather different. The evolution of BIM uses from buildings to infrastructure projects is also discussed. The research presented can provide insightful references for the future adoption and use of BIM in other infrastructure projects.